ANALISIS MUATAN NILAI FILOSOFIS DALAM PENGEMBANGAN MATA PELAJARAN BAHASA INDONESIA DI SEKOLAH: KAJIAN FILSAFAT - M. Furqon Al Maarif; Santika Dewi Lestari; Inggrid Amanda Muharramah; Sarwiji Suwandi; Atikah Anindyarini (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2026)
Indonesian language education in schools not only develops linguistic skills but also integrates ethical values to shape students’ character. This study examines how ethical content is embedded within Indonesian language curricula across elementary, junior high, and senior high school levels from a philosophical perspective, focusing on the dimensions of logic, ethics, and aesthetics. Using a qualitative approach with literature review, this analysis finds that the 2013 Curriculum (K13) explicitly incorporates moral and ethical values through core competencies and character education, while the Merdeka Curriculum emphasizes the Profil Pelajar Pancasila (Pancasila Student Profile) to foster virtuous character, critical thinking, and cultural appreciation. Logical reasoning is cultivated through language activities (e.g., argumentative writing and critical reading), ethical values are imparted via character-infused learning objectives and respectful communication norms, and aesthetic appreciation is developed through engagement with literary works. The integration of these philosophical dimensions in Indonesian language learning is intended to produce students who are not only linguistically competent but also morally upright and appreciative of cultural beauty. The findings highlight that effective Indonesian language teaching harmonizes truth-seeking (logic), goodness (ethics), and beauty (aesthetics) as fundamental educational values.